Mechanical and Thermal Properties of Graphene over Composite Materials: A Technical Review - Islam, Md. Mashrur; Ahmed, Sadman Saffaf; Rashid, Moshiur; Akanda, Md. Masum (Journal of Casting & Materials Engineering, 2019)
The recent years have seen numerous developments in the research and headway of graphene, the thinnest two-dimensional nuclear material. Graphene-based materials and their composites have promising applications in an extensive variety of fields; for example, gadgets, biomedical guides, films, adaptable wearable sensors, and actuators. The most recent investigations and movement in this branch of knowledge regularly deliver conflicting or uncertain outcomes. This article evaluates and outlines the distributed information in order to give a basic and complete diagram of the cutting edge. Initially, the particular basic nature of accessible graphene materials is illustrated as well as the distinctive generation methods accessible thus far. The appraisal at that point talks about the different composites that center diverse sub-practical routines; for example, mechanical and aggregate utilitarian applications (e.g., vitality, hardware biomedical, layers, and sensors). The use of graphene and its subsidiaries in the fabricate of nanocomposites with various polymer frameworks has been inspected. And finally, an ending and point of view are given to talking about the rest of the difficulties for graphene nanocomposites in useful science and building.